2007
DOI: 10.1007/s10792-007-9047-8
|View full text |Cite
|
Sign up to set email alerts
|

Active ocular toxoplasmosis in Turkish patients: a report on 109 cases

Abstract: Most of the patients with active ocular toxoplasmosis have asymptomatic retinochoroidal scars. Proximity of active lesions to the scars, and especially to those of the most recent episode, may have implications for treatment. Although the recurrence risk is high, the visual prognosis is good in most patients with typical ocular toxoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
3
18
0
1
Order By: Relevance
“…The 1.7% of cataract was similar to the findings of Balasundaram et al 30 and Tugal-Tutkun et al, 26 but considerably lower than the 13% reported by Bosch-Driessen et al; 5 the comparatively high rate of complications in the latter series is presumably due to the longer follow-up. Interestingly, although raised IOP is often associated with an OT episode 23,29,30 glaucoma as a complication is rare; that is, in the study of TugalTutkun et al, although an IOP rise was seen in 8% patients during active OT, there was no case of glaucoma as a complication, 26 nor was it seen in the series of Balasundaram et al 30 In our series, one case was complicated by glaucoma secondary to OT.…”
Section: Eyesupporting
confidence: 80%
See 2 more Smart Citations
“…The 1.7% of cataract was similar to the findings of Balasundaram et al 30 and Tugal-Tutkun et al, 26 but considerably lower than the 13% reported by Bosch-Driessen et al; 5 the comparatively high rate of complications in the latter series is presumably due to the longer follow-up. Interestingly, although raised IOP is often associated with an OT episode 23,29,30 glaucoma as a complication is rare; that is, in the study of TugalTutkun et al, although an IOP rise was seen in 8% patients during active OT, there was no case of glaucoma as a complication, 26 nor was it seen in the series of Balasundaram et al 30 In our series, one case was complicated by glaucoma secondary to OT.…”
Section: Eyesupporting
confidence: 80%
“…22,26 However, the rate of vitritis was lower than generally reported, 22,26,29,30 which may suggest that the level of vitreous haze was not always reliably recorded, particularly if low.…”
Section: Eyementioning
confidence: 83%
See 1 more Smart Citation
“…Tugal-Tutkun et al published data on 109 Turkish patients with ocular toxoplasmosis [14]. Patients were treated with trimethoprim-sulfamthoxazole, clindamycin, clarithromycin, spiramycin, and/ or azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a study co ve ring 109 ac ti ve OT pa ti ents, SMD has not be en re por ted in any of the se pa ti ents. 6 Inf lam ma ti on af fec ting the uve a can pre sent with dif fu se ma cu lar ede ma, cysto id ma cu lar edema or SMD type flu id ac cu mu la ti ons. 7,8 Ho we ver, we do not know which fac tors influence the ap pea ran ce of the se cli ni cal sta tes.…”
Section: Discussionmentioning
confidence: 99%